Mini Tinjauan Literatur Keefektifan Penggunaan Aplikasi Mathway Dalam Pembelajaran Matematika - Vania Retna Syahrani; Yahfizham Yahfizham (Pusat Riset dan Inovasi Nasional, 2024)
Mathematics learning is one of the lessons with abstract concepts that require students to solve problems on math problems in everyday life. In learning mathematics, educators can utilize applications or technology today as learning media such as mathway. Mathway application not only provides answers but provides a discussion of math problems in great detail. This study uses a literature review method that aims to investigate the effectiveness of using the Mathway application in learning mathematics. There are 6 national articles from google scholar that are relevant to the use of Mathway application in learning mathematics. The results of this study prove that the use of Mathway application is effective in learning mathematics because it can help students or teachers in understanding math learning. Mathway application is also effective on students' motivation, numeracy literacy, and critical thinking skills in learning mathematics.